Keteladanan Guru dalam Pembentukan Karakter Islami Anak usia Dini di PAUD IT Bunayya Pekanbaru - ajriahmuazimah; Ida Windi Wahyuni; Suyadi Suyadi (UIR PRESS, 2022)
The purpose of this study was to determine the teacher's example in forming the Islamic character of PAUD IT Bunayya Pekanbaru students. This type of research is descriptive qualitative research. Data collection techniques using observation, interviews, and documentation. Analyzed using the Miles & Huberman technique, the validity of the data using data triangulation. The location of this research is in PAUD IT Bunayya Jalan Putra Panca Sei Mintan Simpang Tiga Pekanbaru Village, with six research subjects namely, the principal, and 5 class teachers. The results of this study indicate that the example displayed by the teacher is an effective way to form students' Islamic character, as can be seen that Islamic character is already attached to students, so that students implement these character values ​​in everyday life. Efforts made by teachers and schools so that Islamic character values ​​are attached to children are through example, consistent habituation, giving praise and motivation, evaluating teacher performance, reflection and building good cooperation with parents. Based on the results of the research that has been obtained, it can be concluded that the role model is a very appropriate and effective method to shape the Islamic character of early childhood, because the values ​​of the Islamic character are internalized in the child directly.